Saccharification of rice straw by cellulase from a local Trichoderma harzianum SNRS3 for biobutanol production - Rahnama, Nooshin; Foo, Hooi Ling; Abdul Rahman, Nor'aini; Ariff, Arbakariya; Md. Shah, Umi Kalsom (BioMed Central, 2014)
Background: Rice straw has shown to be a promising agricultural by-product in the bioconversion of biomass to value-added products. Hydrolysis of cellulose, a main constituent of lignocellulosic biomass, is a requirement for fermentable sugar production and its subsequent bioconversion to biofuels such as biobutanol. The high cost of commercial enzymes is a major impediment to the industrial application of cellulases. Therefore, the use of local microbial enzymes has been suggested. Trichoderma harzianum strains are potential CMCase and β-glucosidase producers. However, few researches have been reported on cellulase production by T. harzianum and the subsequent use of the crude cellulase for cellulose enzymatic hydrolysis. For cellulose hydrolysis to be efficiently performed, the presence of the whole set of cellulase components including exoglucanase, endoglucanase, and β-glucosidase at a considerable concentration is required. Biomass recalcitrance is also a bottleneck in the bioconversion of agricultural residues to value-added products. An effective pretreatment could be of central significance in the bioconversion of biomass to biofuels. Results: Rice straw pretreated using various concentrations of NaOH was subjected to enzymatic hydrolysis. The saccharification of rice straw pretreated with 2% (w/v) NaOH using crude cellulase from local T. harzianum SNRS3 resulted in the production of 29.87 g/L reducing sugar and a yield of 0.6 g/g substrate. The use of rice straw hydrolysate as carbon source for biobutanol fermentation by Clostridium acetobutylicum ATCC 824 resulted in an ABE yield, ABE productivity, and biobutanol yield of 0.27 g/g glucose, 0.04 g/L/h and 0.16 g/g glucose, respectively. As a potential β-glucosidase producer, T. harzianum SNRS3 used in this study was able to produce β-glucosidase at the activity of 173.71 U/g substrate. However, for cellulose hydrolysis to be efficient, Filter Paper Activity at a considerable concentration is also required to initiate the hydrolytic reaction. According to the results of our study, FPase is a major component of cellulose hydrolytic enzyme complex system and the reducing sugar rate-limiting enzyme. Conclusion: Our study revealed that rice straw hydrolysate served as a potential substrate for biobutanol production and FPase is a rate-limiting enzyme in saccharification.